The Effect of the Project Based Learning (PjBL) Model on Students’ Critical Thinking Skills in Physics - Nurnabilah, Nurnabilah; 'Ardhuha, Jannatin; Wahyudi, Wahyudi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to examine the effect of the Project Based Learning (PjBL) model on students’ critical thinking skills in physics, particularly on the topic of particle dynamics. This research employed a quasi-experimental method with a nonequivalent control group design. The population consisted of all eleventh-grade students of Senior High School 10 Mataram in the 2025/2026 academic year, totaling 53 students. The sample was selected using a saturated sampling technique, resulting in 28 students from class XI MIPA 1 as the experimental group and 25 students from class XI MIPA 2 as the control group. The experimental group was taught using the Project Based Learning (PjBL) model, while the control group received instruction through a conventional learning model. The results of the analysis showed that the average score of students’ physics critical thinking skills in the experimental group was 78.57, which falls into the critical category, while the control group achieved an average score of 72.22, categorized as moderate. The instrument used to measure critical thinking skills consisted of six essay questions. Hypothesis testing was conducted using a pooled variance t-test with the criterion that if the calculated t-value exceeds the critical t-value, the alternative hypothesis is accepted and the null hypothesis is rejected. The t-test results indicated a calculated t-value of 2.29, which is greater than the critical t-value of 2.01 at a significance level of 5 percent. Furthermore, the N-Gain test was applied to determine the improvement in students’ critical thinking skills. The results showed an N-Gain value of 0.68 for the experimental group and 0.57 for the control group, both of which fall into the moderate category. Based on these findings, it can be concluded that the Project Based Learning (PjBL) model has a significant effect on students’ critical thinking skills in physics.